Diodos emissores de luz (LED) vermelho para melhorar a eficiência da terapia com células tronco mesenquimais - Mansano, Bárbara Sampaio Dias Martins (2020)
Mesenchymal stem cells (MSC) are widely used in the treatment of various genetic or acquired diseases, and can be found in bone marrow, adipose tissue, umbilical cord blood and placenta. It is believed that the benefits of transplanting MSCs are mainly based on the action of paracrine factors in the microenvironment, participating in local cell proliferation, angiogenesis, immunosuppression, and attenuation of apoptosis and the formation of fibrosis. However, the low survival rate of transplanted cells and poor grafting are still problems to be overcome. Cellular decrease can occur due to mechanical stress inherent to the preparation of the injection suspension, immune rejection, poor adherence of MSCs to tissue and cell death caused by the hostile microenvironment of the transplanted site. Thus, in this study, we irradiate MSCs with light emitting diodes (LED), looking for positive changes in cell metabolism and in the secretion of cytokines and growth factors to improve the efficiency of existing cell therapy. MSC derived from adipose tissue (CTMA) were obtained from male Fischer-344 rats and two variants were analyzed: the repercussion of different radiant exposures (0.5, 2 and 4 J/cm²) and the influence of the number of irradiations (dose single or once every two days, totalizing three irradiations), using irradiance of 15 mW/cm² and LEDbox of 630 nm (Biolambda, Brazil). The control group was kept in the dark for the same time as the 4 J/cm² group and the analyzes were performed 24 hours after the last irradiation. With that, we obtained that the multiple irradiations had a better influence on the MSC compared to the single irradiation. None of the radiant exposures induced oxidative stress, either in the concentrations of oxidized proteins and MDA, DNA damage or changes in cell proliferation and TNF-α secretion and cell adhesion proteins ICAM-1 and L-selectin. The use of 0.5 and 2 J/cm² led to a decrease in mitochondrial breathing under metabolic stress from baseline, maximum and proton leakage. Still in the group that received 0.5 J/cm² irradiation, a significant increase in VEGF levels was observed, but a negative regulation at the IL-10 level in relation to the non-irradiated group. Irradiation with 4 J/cm² improved mitochondrial activity in MTT markers and AlamarBlue, the production of ATP and the secretion of IL-6, IGF-1 and NOx index in relation to Ct. We conclude, then, that conditioning with multiple irradiations of 4 J/cm² presented the best results for improving the metabolism and the possible paracrine effects of MSCs, being a good candidate for future cell therapy.